The Power Of Friendship Reflected In The Land Of Five Towers Novel (2011): A Psychoanalytic Approach - Wibowo, Nasib Wahyu, Drs. Abdillah Nugroho, M.Hum, Siti Fatimah, S.Pd, M.Hum (2013)
The problem of this study is the power of friendship to conviction for success is reflected in Ahmad Fuadi's The Land of Five Towers novel. The objective of this study is to analyze the novel based on the structural elements and to analyze the novel based on the psychoanalytic approach. The type of this research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is The Land of Five Towers novel writen by Ahmad Fuadi in 2011. While the secondary data sources are other materials taken from author's biography, essay, comments, criticism and internet related to the study. Both data are collected by conducting library research and analyzed by descriptive analysis. Based on the analysis, the writer portrays some conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, setting, plot, point of view, theme, are supporting each other to produce a good qualifies novel. Second, based on the psychoanalytic analysis, the study shows that the problem faced by the major character is his own psychological condition to decide the appropriate ways for his life. This novel also shows the process that conviction for success with the power of friendship.